The Effects of Apigenin on the Expression of Fas/FasL Apoptotic Pathway in Warm Liver Ischemia-Reperfusion Injury in Rats. (6th July 2014) - Tsalkidou, Evanthia G.; Tsaroucha, Alexandra K.; Chatzaki, Ekaterini; Lambropoulou, Maria; Papachristou, Fotini; Trypsianis, Gregory; Pitiakoudis, Michael; Vaos, Georgios; Simopoulos, Constantinos
Abstract : Background . The aim of this experimental study was to investigate the role of apigenin in liver apoptosis, in an experimental model of hepatic ischemia-reperfusion in rats. Materials and Methods . Forty-eight Wistar rats (apigenin and control groups), 14 to 16 weeks old and weighing 220 to 350 g, were used. They were all subjected to hepatic ischemia by occlusion of the hepatic artery and portal vein for 45 minutes and reperfusion was followed for 60, 120, and 240 minutes. Apigenin was administrated intraperitoneally. Liver tissues were used for the detection of apoptosis by TUNEL assay and caspase 3 antibodies. Expression analysis of Fas/FasL genes was evaluated by real time PCR. Results . The expression analysis of Fas and FasL genes was increasing during reperfusion (significantly in the group of 240 minutes of reperfusion). It was in the same group that apigenin decreased Fas receptor levels and inhibited apoptosis as confirmed by TUNEL assay and caspase 3 antibodies. Conclusions . The effects of apigenin in the Fas/FasL mediated pathway of apoptosis, in the hepatic ischemia-reperfusion, seem to have a protective result on the hepatic cell.